Interplay between stochastic and deterministic processes in the maintenance of alternative community states in Verrucomicrobia-dominated shallow lakes - Llames, Maria Eugenia del Rosario (2017)
We analyzed the interplay between neutral and deterministic processes in maintaining contrasting alternative bacterioplankton communities through time in highly productive shallow lakes and evaluated the relevance of these processes when a regime shift from a clear to a turbid state occurred. We observed that local assembly is ruled primary deterministically, via local habitat filtering, with a secondary role of stochastic processes. We also found a hierarchy in the environmental sorting: while an unusual Verrucomicrobia dominance characterizes the three systems, local conditions limit within-bacterial community membership to closely phylogenetically related and ecologically similar taxa. These results indicate that bacterial abilities to establish in these lakes are strongly determined by their traits, and point toward special physiological adaptations to persist when these systems undergo a regime shift. Altogether, these results hint to a divergence in function among these alternative communities, mediated by major shifts in bacterial community trait structure, particularly regarding carbon use.